Does moral distress in emergency department nurses contribute to intentions to leave their post, specialisation, or profession: A systematic review - Olivia Boulton; Barbara Farquharson (Elsevier, 2024)
Background: There is a global shortfall of nurses. Despite national targets to increase nurse training and retention, the numbers leaving the profession continue to rise. Emergency departments (EDs) consistently record above average staff-turnover. Meanwhile descriptions of moral distress amongst emergency nurses are increasing. It is vital to consider the long-term emotional and psychological impact of moral distress on the emergency nursing workforce. However, the events which trigger moral distress in the emergency department may differ from those described in other clinical areas. A clearer understanding of the effects of moral distress on intention to leave could help identify those at risk and inform decisions on interventions designed to mitigate moral distress, aiding nurse retention and the organisational stability of health services. Aim: This systematic review aims to synthesise the available evidence on the association between moral distress and intention to leave in emergency nurses. Methods: A systematic search of studies was performed on MEDLINE, CINAHL, PsychINFO, Web of Science and Cochrane databases (8th -10th June 2022). Results were screened and quality-assessed with cross-checks. The heterogeneity of samples and insufficient data precluded statistical pooling and meta-analysis. Consequently, narrative synthesis was performed. Results: Five studies reported quantitative results eligible for synthesis. Low to moderate levels of moral distress were reported in emergency nurses; contrasting starkly with the significant proportion who reported having left or considered leaving due to moral distress (up to 51%). Sparse, mostly low-quality evidence was identified, highlighting a need for more robust research. Current tools for measuring moral distress appear not to capture the unique pressures which contribute to moral distress in emergency nurses. Conclusions: Emergency nurses cite moral distress as a reason for leaving. Further study is required to determine the levels of moral distress associated with intentions to leave and the strength of that association. This is fundamental to the design of effective retention policies. Future research should also explore the applicability of current moral distress measures to the emergency department, with consideration given to developing emergency department specific tools. PROSPERO Registration number: CRD42022336241 https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=336241